Linux shell scripting cookbook : over 110 incredibly effective recipes to solve real-world problems, automate tedious tasks, and take advantage of Linux's newest features /: over 110 incredibly effective recipes to solve real-world problems, automate tedious tasks, and take advantage of Linux's newest features. (2017) - Flynt, Clif; Tushar, Shantanu; Lakshman, Sarath
No abstract available